A DESCRIPTIVE STUDY OF STUDENTS LEARNING STYLE IN ONLINE ENGLISH LEARNING AT THE FIFTH SEMESTER ENGLISH EDUCATION STUDY PROGRAM IN MUHAMMADIYAH KOTABUMI UNIVERSITY ACADEMIC YEAR 2021/2022 - Sugitriyani, Armi; Susilowati, Rini; Suprapto, Irawan (Griya Cendikia, 2022)
Online learning is a distance learning process without meeting face to face in a study room, so that the delivery of material uses electronic media and the internet as access in the learning process. In the learning process there are several factors that affect the effectiveness in the learning process, one of which is learning styles namely, visual, auditory, and kinesthetic. Therefore, this study aims to determine what types of learning styles are used by students in online English learning and what the dominant types of students’ learning style. This research uses quantitative descriptive research, and a population of 41 students at the fifth semester of English Education Study Program, Muhammadiyah Kotabumi University academic year 2021/2022. The sample is taken from the entire population data using a total sampling technique. In collecting data, the researcher used a closed questionnaire with a Likert scale. Based on the results of data analysis using statistical data analysis methods consisting of the mean, median, mode and standard deviation, the results showed that in online English learning process students have visual learning styles were 10 students (24.4%), auditory learning styles were 6 students (14.6%), kinesthetic learning styles were 15 students (36.6%). Also found that there was a variation of learning styles between two learning styles, namely, visual-auditory (7.3%), visual-kinesthetic as many as 3 students (7.3%) and auditory learning styles as many as 4 students (9.8%). In addition, the dominant type of learning style used by students in online English learning at the fifth semester English Education study program in Muhammadiyah Kotabumi University academic year 2021/2022, is the kinesthetic learning style with 15 students (36.6%).